ClaPEPCK4: target gene for breeding innovative watermelon germplasm with low malic acid and high sweetness - Congji Yang; Jiale Shi; Yuanyuan Qin; ShengQi Hua; Jiancheng Bao; Xueyan Liu; Yuqi Peng; Yige Gu; Wei Dong (GM Crops & Food)
Malic acid markedly affects watermelon flavor. Reducing the malic acid content can significantly increase the sweetness of watermelon. An effective solution strategy is to reduce watermelon malic acid content through molecular breeding technology. In this study, we measured the TSS and pH of six watermelon varieties at four growth nodes. The TSS content was very low at 10 DAP and accumulated rapidly at 18, 26, and 34 DAP. Three phosphoenolpyruvate carboxykinase (PEPCK) genes of watermelon were identified and analyzed. The ClaPEPCK4 expression was inversely proportional to malate content variations in fruits. In transgenic watermelon plants, overexpressing the ClaPEPCK4 gene, malic acid content markedly decreased. In the knockout transgenic watermelon plants, two SNP mutations and one base deletion occurred in the ClaPEPCK4 gene, with the malic acid content in the leaves increasing considerably and the PEPCK enzyme activity reduced to half of the wild-type. It is interesting that the ClaPEPCK4 gene triggered the closure of leaf stomata under dark conditions in the knockout transgenic plants, which indicated its involvement in stomatal movement. In conclusion, this study provides a gene target ClaPEPCK4 for creating innovative new high-sweetness watermelon varieties.